A Rare Case of Intracranial Metastasis of Chondroblastic Osteosarcoma from Lungs: A Case Report and Review of Literature - Goyal, Sarvesh; Pandey, Kushagra; Meena, Rajesh; Gurjar, Hitesh Kumar; Das, Sumanto; Sharma, M.C. (Indian Journal of Neurosurgery, 2025)
Osteosarcoma are the most common primary bone tumors in children and adolescents. Brain metastases of osteosarcoma is usually a terminal event in the disease course. Surgical resection of the brain metastatic lesion forms the mainstay of treatment with chemotherapy and radiotherapy as add-ons. We present the case of a 57-year-old woman who presented with complains of breathlessness and headache. Contrast-enhance computed tomography (CECT) showed a large left lung mass. Magnetic resonance imaging (MRI) of the brain depicted an anterior temporal space occupying lesion. The patient underwent surgical removal of the mass lesion, with biopsy revealing the diagnosis as chondroblastic osteosarcoma.
Keywords: osteosarcoma; chondroblastic; metastases